Curcuma leonidii, a new species from southern Vietnam - Leong-Škorničková, J.; Lưu, Hồng Trường (Phytotaxa, 2013)
Curcuma leonidii, a new species of Curcuma subg. Hitcheniopsis (Zingiberaceae) from southern Vietnam is described and illustrated here. Curcuma leonidii with flowers similar to some Stahlianthus-like species but inflorescences consisting of up to 8 green bracts and their arrangements conforming to usual ‘classical’ Curcuma-like species provides the much-awaited morphological link between the two genera, of which Stahlianthus have been, based on molecular results, recently proposed to be merged with Curcuma subg. Hitcheniopsis.